(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Laparoscopic surgery is now-a-days an established treatment option for diseases like Cholelithiasis, Appendicitis, Hernia etc. But laparoscopy also has a definite role in diagnosis of abdominal diseases. In many cases diagnostic dilemma remains after all basic investigations are done. In some cases clinical findings and investigation findings get contradictory. In both these issues, laparoscopy can play a vital role to achieve a specific diagnosis. In some cases tissue sample can also be obtained for histological diagnosis. Methods: It was a prospective cross-sectional study of 60 patients selected by randomized sampling method, both male & female, of various abdominal conditions who couldn’t be diagnosed by conventional interventions & gave informed written consent. It was done over two years period. We excluded patients with uncontrolled coagulopathy, hemodynamicaly unstable patients, patients having undergone multiple previous laparotomies and all patients younger than 12 years. Then the initial diagnosis, the laparoscopic diagnosis and the subsequent outcome of this group of patients were evaluated. Results: A definitive diagnosis was made in 86.66%( 52) of cases after laparoscopy while 13.34% (8) cases had no obvious pathology. Laparoscopy changed the clinical diagnosis in 20% (12) cases. Laparoscopic biopsy was taken in 18.33% (11) cases. Mean Operation time was 20 minutes. Conclusion: Diagnostic laparoscopy is a simple, rapid, effective and accurate tool in evaluating patients with various abdominal conditions in whom conventional methods of investigation have failed to elicit a certain cause. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 31-35